2021
DOI: 10.1002/ejic.202100612
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dependence of the Luminescent Properties of Mononuclear TbIII Macrocyclic Complexes

Abstract: A family of six terbium(III) complexes with hexaaza macrocyclic ligands, together with the isostructural yttrium(III) species, is reported and the thermal dependence of the photophysical properties of the terbium(III) complexes is analysed. The coordination number is defined by the anions, nitrate or isothiocyanate, which act as secondary ligands. While complexes with nitrate anions are decacoordinated species, presenting a N 6 O 4 first coordination sphere, complexes derived from isothiocyanate are nonacoordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Reagent grade chemicals and HPLC quality solvents were used as received. The synthesis of erbium(III) complexes 1-3 was performed according to the reported procedures 19,20 (see the ESI †).…”
Section: Synthesismentioning
confidence: 99%
“…Reagent grade chemicals and HPLC quality solvents were used as received. The synthesis of erbium(III) complexes 1-3 was performed according to the reported procedures 19,20 (see the ESI †).…”
Section: Synthesismentioning
confidence: 99%
“…For Dy-EDA , a broad band with a maximum at 425 nm was also observed, which is related to the ligand emission. This was corroborated by comparing with the emission spectrum of the Y III analogue . The intensity of the ligand emission band of Dy-EDA is greater than the characteristic emission bands of the Dy III ion, indicating that the energy transfer mechanism from the ligand to the lanthanide is inefficient.…”
Section: Resultsmentioning
confidence: 64%
“…This was corroborated by comparing with the emission spectrum of the Y III analogue. 20 The intensity of the ligand emission band of Dy-EDA is greater than the characteristic emission bands of the Dy III ion, indicating that the energy transfer mechanism from the ligand to the lanthanide is inefficient. Conversely, Dy-DAP did not show bands related to ligand emission, evidencing that the ligand acts as an efficient antenna in the sensitization of Dy III luminescence.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…21 In this way, these macrocyclic ligands have been used as chromophores in luminescence studies and depending on the lateral spacer on the macrocycle they have been shown to act as efficient "antennas" in the luminescence of Ln III ions. [22][23][24][25] According to these reports, [2 + 2] Schiff-base macrocycles with 3-carbon chain lateral spacers are better antennas that those with 2-carbon ones, while the use of axial nitrate anions showed an increase of the luminescence in these systems. These features are in direct contrast to the design strategies previously discussed for a high performance SMM: the weak crystal field of axial nitrate anions and higher macrocycle distortion due to the length of the lateral spacer.…”
Section: Introductionmentioning
confidence: 99%